Portage : A Family, a Canoe, and the Search for the Good Life - Leaf, Sue, 1953- (Book collections on Project MUSE., 2015)
Part travelogue, part natural and cultural history, Portage is the memoir of one family's 35-year venture into the watery expanse of the world. Exploring the river means encountering the inevitable changes that occur as a family canoes through time and learns what it means to be human in this natural world.